Sviluppare competenze in intercomprensione di livello avanzato - Garbarino, Sandra (Educazione Linguistica Language Education, 2019)
The present paper discusses the progression of interaction skills in contexts of intercomprehension mediated by ICT (forums, chats and VoIP). It illustrates how the Language Centre of Lyon 2 University faced the challenge of creating a pluriannual course of intercomprehension among Romance languages integrated into the academic curriculum. This important acknowledgement, related to the linguistic policy of the university, naturally led to the creation of a syllabus extended over 4 semesters. The courses outline was structured by taking into account the descriptors of the REFIC (Référentiel de compétences de communication en intercompréhension), the literature on curricular integration of intercomprehension and the results of action-research.